The Urgency of Impostor Phenomenon in Educational Institutions - Mutiara Aqilla Tasya; Juntika Nurihsan; Eka Sakti Yudha; Philein Sophia Putri Dakes; Rifqi Fadhillah Farmadi (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
The impostor phenomenon is a unique phenomenon that occurs in high achieving individuals. The impostor phenomenon can affect a person's psychological well-being, such as work, academics, interpersonal relationships, or the ability to achieve self-actualization. This research aims to look at the description and urgency of the impostor phenomenon among students. This research uses literature study methods in various journals, book chapters, theses such as Science Direct, Psyc Info, Sage, and Taylor & Francis, and the Online Thesis database. The results of research from 9 selected pieces of literature showed that students often experience the impostor phenomenon in the "medium" and "high" categories. The demands of the academic environment, such as high competition and self-comparison are the main triggers. High achieving students tend to feel anxious, afraid of disappointing others, and doubtful when achieving success. Therefore, there is a need for counselor action to overcome the problem of this impostor phenomenon by educating on the impact and carrying out interventions. Cognitive restructuring techniques are recommended to help overcome the impostor phenomenon problem. Keywords: impostor phenomenon, student, counseling guidance